Pengaruh Kemudahan Mengakses E-Commerce Dan Pembayaran Digital Terhadap Perilaku Konsumtif Remaja Generasi Z di Kelurahan Grati Tunon Kecamatan Grati Kabupaten Pasuruan - Salmita, Fajrin A’yun; Pradikto, Sugeng; Suchaina, Suchaina (STIE Semarang, 2024)
This research aims to determine the partial or simultaneous affect of the variables of ease of accessing e-commerce (X1) and digital payments (X2) on the consumptive behavior (Y) of Generation Z teenagers, Grati Tunon Village, Grati District, Pasuruan Regency.With technological developments, e-commerce applications and digital payments are widely used by Generation Z teenagers in making transactions or buying and selling. The convenience offered by this application triggers consumptive behavior among Generation Z teenagers. Consumptive behavior is the behavior of consuming excessive amounts of goods that are not needed just for desires.This research uses quantitative research methods, data collection uses a questionnaire distributed to 90 respondents. Data processing uses SPSS software and is analyzed using validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple linear regression tests and hypothesis tests.The results of the research show that (1) There is a partial affect of the ease of accessing e-commerce on the consumptive behavior of Generation Z teenagers in Grati Tunon Village, Grati District, Pasuruan Regency. (2) There is a partial affect of digital payments on the consumptive behavior of Generation Z teenagers in Grati Tunon Village, Grati District, Pasuruan Regency. (3) There is an affect of the ease of accessing e-commerce and digital payments simultaneously on the consumptive behavior of Generation Z teenagers in Grati Tunon Village, Grati District, Pasuruan Regency. It is hoped that future researchers will be able to explore other factors that can affect consumptive behavior among Generation Z teenagers.